KARAKTERISASI MOLEKULER TANAMAN SAMBUNG NYAWA (Gynura procumbens [Lour.] Merr) BERDASARKAN 18S rRNA - Octavia Dewi Christiningrum; Anto Budiharjo; Endang Kusdiyantini (Jurnal Akademika Biologi, 2016)
Sambung Nyawa (Gynura procumbens) is a traditional medicinal plant used by people as an antihyperglycemic drug, antihyperlipidemic and chemoprevention agents. Comprehensive information on this plant needs to be done, including DNA analysis, so it can complement morphological character of an organisms. This study aimed to molecularly characterize and determine the relationship between G. procumbens with other organisms using ribosomal 18S rRNA gene. PCR (Polymerase Chain Reaction) was used to amplify the 18S rRNA gene fragments G. procumbens. DNA sequences were analyzed using the BLAST program at the NCBI portal and construction of phylogenetic trees were tested using Bootstrap method 1000x. The results showed the 18S rRNA sequence of Gynura procumbens fragments was 1600 bp, and G. procumbens belonged in the family of Asteraceae.Key words : Gynura procumbens, PCR (Polymerase Chain Raction), 18S rRNA, Bootstrap method